2019
DOI: 10.1021/acs.nanolett.9b00729
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High, Strongly Temperature Dependent, Spin Hall Conductivity of SrRuO3

Abstract: Spin-orbit torques (SOT) in thin film heterostructures originate from strong spin-orbit interactions (SOI) that, in the bulk, generate a spin current as the result of extrinsic spindependent, skew or/and side-jump, scattering, or in the intrinsic case due to Berry curvature in the conduction band. While most SOT studies have focused on materials with heavy metal components, the oxide perovskite SrRuO3 has been predicted to have a pronounced Berry curvature. Through quantification of its spin current by the SOT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 58 publications
4
59
0
3
Order By: Relevance
“…11). In FM systems, the unusual sz has been attributed to the spin-orbit precession [12], the spin rotation symmetry [14], the AMR effect and the anomalous Hall effect [15,16,38]. These processes require the net magnetization of FM and sz is very sensitive to interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…11). In FM systems, the unusual sz has been attributed to the spin-orbit precession [12], the spin rotation symmetry [14], the AMR effect and the anomalous Hall effect [15,16,38]. These processes require the net magnetization of FM and sz is very sensitive to interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, sizable SOT has been observed experimentally in both SrIrO 3 and SrRuO 3 . [ 36–38 ] Variations of the SOT efficiency with the thickness of SrIrO 3 and SrRuO 3 were attributed to the thickness‐dependent octahedral rotation. [ 36,38 ] However, the relation between the octahedral rotation and SOT is still blurred due to limited evidences.…”
Section: Figurementioning
confidence: 99%
“…In particular, 5d transition metal oxides (TMO), with strong SOC and electron–electron correlation, give rise to intriguing fundamental physics, ranging from nontrivial quantum phases [ 28–30 ] to magnetic anisotropy manipulation [ 31 ] and intrinsic charge‐spin interconversion. [ 32–35 ] However, despite this rich physics, in the few room temperature studies on charge‐spin interconversion in 5d TMOs, the adjacent FM metal has typically been a non‐epitaxial metal, such as SrIrO 3 (SIO)/Permalloy (Py), [ 32,33 ] SIO/Co 1− x Tb x , [ 34 ] and SrRuO 3 /Co. [ 35 ] The resulting SOT efficiencies, ξ || ≤ 1, [ 32–35 ] are comparable to their HM/FM counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32–35 ] However, despite this rich physics, in the few room temperature studies on charge‐spin interconversion in 5d TMOs, the adjacent FM metal has typically been a non‐epitaxial metal, such as SrIrO 3 (SIO)/Permalloy (Py), [ 32,33 ] SIO/Co 1− x Tb x , [ 34 ] and SrRuO 3 /Co. [ 35 ] The resulting SOT efficiencies, ξ || ≤ 1, [ 32–35 ] are comparable to their HM/FM counterparts. With this as the background, our hypothesis was that creating atomically perfect ferromagnet and SOC metal layers, coupled through chemically abrupt epitaxial interfaces, can lead to emergent electronic phenomena at the interfaces, [ 31 ] as well as the opportunity to obtain more efficient charge‐to‐spin conversion.…”
Section: Introductionmentioning
confidence: 99%